Politik Dinasti dalam Perspektif Psikologi Politik: Tinjauan Sistematis Kepercayaan Politik - Alen Veranika Wati; Amanda Aulia Putri; Fitrisya Aura Delia; Hassya Padmasari; Nurul Fitriani; Khoiriya Ulfah (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Dynastic politics, a phenomenon in which political power is inherited within a single family, has been a growing concern in many democracies, including Indonesia. This study aims to examine the psychological dimensions of dynastic politics, particularly its relationship with political trust among citizens. Using a systematic literature review (SLR) approach, this study analyzed 24 articles published between 2021 and 2026 from databases such as Scopus, Web of Science, and Google Scholar. The inclusion criteria focused on studies addressing political dynasty, political trust, and related psychological constructs within democratic contexts. Findings indicate that dynastic politics significantly undermines political trust due to perceptions of nepotism, elite entrenchment, and reduced political efficacy among citizens. Furthermore, political psychology literature reveals that emotional responses such as cynicism, frustration, and disillusionment mediate the relationship between dynastic political practices and declining trust in institutions. This study also highlights that social identity theory and institutional trust frameworks are the most frequently applied theoretical lenses in this domain. The results contribute to the understanding of how dynastic politics shapes political psychology and suggest the need for structural reforms to restore political trust and democratic legitimacy.